Amphiphilic mPEG-PLGA copolymer nanoparticles co-delivering colistin and niclosamide to treat colistin-resistant Gram-negative bacteria infections - Kaifang Yi; Xilong Wang; Pengliang Li; Yanling Gao; Dandan He; Yushan Pan; Xiaoyuan Ma; Gongzheng Hu; Yajun Zhai (Communications Biology)
Abstract Colistin is the last line of defense against multidrug-resistant (MDR) Gram-negative bacterial infections, yet it is restricted due to high drug resistance and toxicity. The combination therapy of colistin and niclosamide exhibits excellent synergistic antibacterial activity against Gram-negative bacteria. How to co-deliver these two drugs with vastly different pharmacokinetic properties in sufficient amounts to the infection site is the core issue that must be resolved for the clinical translation of this drug combination. Here, we designed and prepared a nanosystem capable of co-loading colistin and niclosamide with different physicochemical properties into mPEG-PLGA nanoparticles (COL/NIC-mPEG-PLGA-NPs) to overcome the resistance of multiple colistin-resistant bacteria to colistin and alleviate its toxicity. Mechanistic studies revealed that the COL/NIC-mPEG-PLGA-NPs enhanced the affinity of delivered COL to the modified membrane of colistin-resistant bacteria. The increased membrane permeability caused by colistin promotes an influx of niclosamide, which reduces efflux pump activity and generates intracellular ROS stress, eliminating colistin-resistant bacteria. In addition, the nanoparticles proved non-toxic both in vitro and in vivo. Overall, our study has profound insights into the use of nanosystems with high biosafety for the treatment of infections caused by colistin-resistant bacteria.